Facing Job Uncertainties: The Lived Experiences and Challenges Encountered by Government Contractual Workers - Abanto, Rolando II; Marcelino, Anna Rose; Oyao, Roldan (Journal of Interdisciplinary Perspectives, 2024)
Contractualization remains a contentious issue, particularly in the Philippines, where "Endo" (end of contract) refers to short-term employment. This qualitative phenomenological study aimed to investigate the challenges faced by job-order employees in a Philippine government agency. The study employed a descriptive-phenomenological research design. Eleven individuals employed under job order arrangements participated in semi-structured key informant interviews (KII). The collected data were analyzed using Colaizzi's approach. The results revealed the following themes regarding their challenges: insecurities, pressures, disincentives; work commitment; advancement; and optimism for coping mechanisms. Despite the challenges of job-order employment, the informants managed to perform their assigned services effectively. Additionally, they expressed a desire to become regular government employees. The study recommends that management improve job characteristics and the work environment through clear communication to increase satisfaction and retention. Employees should enhance their qualifications by obtaining master's degrees, specialized training, and attending seminars to improve job stability and prospects for permanent employment. Management should establish a clear path from temporary to permanent roles and implement a fair contract renewal process to promote stability and long-term commitment, reduce social comparison, and increase workplace productivity.